2006
DOI: 10.6004/jnccn.2006.2003
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Testing in Breast Cancer: NCCN Task Force Report and Recommendations

Abstract: The NCCN HER2 Testing in Breast Cancer Task Force was convened to critically evaluate the ability of the level of HER2 expression or gene amplification in breast cancer tumors to serve as a prognostic and a predictive factor in the metastatic and adjuvant settings, to assess the reliability of the methods of measuring HER2 expression or gene amplification in the laboratory, and to make recommendations regarding the interpretation of test results. The Task Force is a multidisciplinary panel of 24 expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 114 publications
2
68
0
4
Order By: Relevance
“…However, at the same time, the cancers detected were potentially treatable ones. The expression of ER and PR is well recognized as a predictive factor for response to tamoxifen [21] and 82% of the screening-detected cancers in women in their 40s were ER-positive and 67% were PR-positive; these findings are similar to the distributions noted in previous studies [21][22][23]. Although almost half our patients with screening-detected breast cancers in their 40s had unknown (n = 18) or indeterminate (n = 1) HER2/neu status (likely because of its relatively recent discovery), 18% had HER2/ neu-positive cancers; this finding is consistent with several studies that have reported HER2/neu positivity in 15-20% of breast cancers [24,25].…”
Section: Discussionsupporting
confidence: 82%
“…However, at the same time, the cancers detected were potentially treatable ones. The expression of ER and PR is well recognized as a predictive factor for response to tamoxifen [21] and 82% of the screening-detected cancers in women in their 40s were ER-positive and 67% were PR-positive; these findings are similar to the distributions noted in previous studies [21][22][23]. Although almost half our patients with screening-detected breast cancers in their 40s had unknown (n = 18) or indeterminate (n = 1) HER2/neu status (likely because of its relatively recent discovery), 18% had HER2/ neu-positive cancers; this finding is consistent with several studies that have reported HER2/neu positivity in 15-20% of breast cancers [24,25].…”
Section: Discussionsupporting
confidence: 82%
“…Trial design, inclusion criteria, and the main clinical results of these trials have been reported previously (19). Briefly, in ABCSG-24, 536 patients with invasive breast cancer were randomly assigned 1:1 to receive six cycles of preoperative epirubicine/docetaxel (both 75 mg/m 2 ) every 3 weeks with or without capecitabine (1,000 mg/m 2 , bid, days [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Patients with HER2-positive disease were further randomized to receive neoadjuvant trastuzumab (8 mg/kg loading dose, then 6 mg/kg every 3 weeks; n ¼ 44) or not (n ¼ 49).…”
Section: Methodsmentioning
confidence: 99%
“…IHC detects the level of HER2 protein expression on the cell surface and allows for a semi-quantitative score ranging from 0 to 3þ, with 3þ indicating a positive HER2 status. ISH, in contrast, identifies the number of HER2 gene copies on chromosome 17 as well as the number of centromere 17 (CEP17) copies per nucleus (14). According to current ASCO/CAP clinical practice guidelines (15), a tumor exhibits HER2 amplification if the HER2/ CEP17 ratio exceeds 2, or absolute HER2 copy number exceeded 6.…”
Section: Introductionmentioning
confidence: 99%
“…Errors may be caused if the period of time for the formalin fixation of tissues is too short or if insufficient quantities of formalin are used 154–157. Other pitfalls related to immunohistochemical testing are nonspecific binding of tissue altered by crush artifact and cautery artifact, factors related to tissue procurement failures 154–160. The American Society of Clinical Oncology (ASCO)‐CAP practice guidelines were published to address these issues 152, 154…”
Section: Evidence For Quality Improvement Opportunities In Oncologic mentioning
confidence: 99%